2019
DOI: 10.7196/samj.2019.v109i3.13510
|View full text |Cite
|
Sign up to set email alerts
|

Venous thromboembolism risk and prophylaxis prescription in surgical patients at a tertiary hospital in Eastern Cape Province, South Africa

Abstract: Background. Venous thromboembolism (VTE) is a common complication during and after hospitalisation, and is regarded as the most common cause of preventable death in hospitalised patients worldwide. Despite its importance, there are few data on VTE risk and adherence to prophylaxis prescription guidelines in surgical patients from the South African (SA) public sector, especially from lowresource environments such as Eastern Cape Province. Objectives. To evaluate the risk and prescription of VTE prophylaxis to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 17 publications
3
14
1
1
Order By: Relevance
“…The ongoing national vaccination survey, the first of its kind since 1994, provides an opportunity for collecting more accurate and nationally representative data. 44 Secondly, the findings of the present study underscore the need to conduct research aimed at unraveling the contextual determinants of poor childhood vaccination uptake at multiple levels and perspectives. This is important to unmask the contextual enablers of geographical disparities in vaccination access, as highlighted by our study.…”
Section: Discussionmentioning
confidence: 80%
“…The ongoing national vaccination survey, the first of its kind since 1994, provides an opportunity for collecting more accurate and nationally representative data. 44 Secondly, the findings of the present study underscore the need to conduct research aimed at unraveling the contextual determinants of poor childhood vaccination uptake at multiple levels and perspectives. This is important to unmask the contextual enablers of geographical disparities in vaccination access, as highlighted by our study.…”
Section: Discussionmentioning
confidence: 80%
“…[3] The therapeutic practice guideline for VTE developed by the Southern African Society of Thrombosis and Haemostasis closely mirrors the ACCP guideline, which bases VTE risk assessment on the Caprini RAM. [2,9] SA has one of the greatest dual burdens of tuberculosis (TB) and HIV infection globally, and both infections have well-established relationships with VTE development. [7] In SA, TB was reported to be the leading cause of death in 2017, and disruptions in TB-related care due to the COVID-19 pandemic have been reported.…”
Section: Researchmentioning
confidence: 99%
“…PE as a complication of VTE is the most preventable cause of inpatient death across the globe. [1,2] VTE is linked to increased healthcare costs, intensive care unit admission and longer hospital stay. [3] Findings from the multinational ENDORSE (Epidemiologic International Day for the Evaluation of Patients at Risk for Venous Thromboembolism in the Acute Hospital Care Setting) study revealed that more than half of all hospitalised patients were at risk for VTE, and 41.5% of these were medical inpatients.…”
mentioning
confidence: 99%
See 2 more Smart Citations